2003
DOI: 10.1080/10273360410001700843
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐Induced Angiogenesis: A Review

Abstract: Angiogenesis, the formation of new blood vessels, has become a broad subject and is a very active area for current research. This paper describes the main biological events involved in angiogenesis and their importance in cancer progression. In the first section, a fundamental overview of tumour biology is presented. In the second section, the biology of healthy blood vessels is described and, in the third section, the mechanisms of cell migration and proliferation, which are crucial to angiogenesis, are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 101 publications
(184 reference statements)
1
54
0
4
Order By: Relevance
“…However, contrary to physiological angiogenesis, the angiogenesis switch continue to be turned on as a result of the persistent manufacturing of angiogenic factors inside the tumor areas that are not sufficiently oxygenated. Constant growth of new capillaries within the tumor results in an imperfect, tortuous, non-mature and leaky vasculature network which is deficient in a stable basement membrane (Plank & Sleeman, 2003).…”
Section: Cancer Pathologymentioning
confidence: 99%
“…However, contrary to physiological angiogenesis, the angiogenesis switch continue to be turned on as a result of the persistent manufacturing of angiogenic factors inside the tumor areas that are not sufficiently oxygenated. Constant growth of new capillaries within the tumor results in an imperfect, tortuous, non-mature and leaky vasculature network which is deficient in a stable basement membrane (Plank & Sleeman, 2003).…”
Section: Cancer Pathologymentioning
confidence: 99%
“…Ethanol extract of S. officinalis exhibited a significant inhibitory activity on the endothelial cells migration as well as on the proliferation of different blood cells, but cell proliferation was supressed only at higher concentration. These findings indicated that anti-angiogenic effect of sage extract might be due to anti-migratory activity [87] attributed to anti-proteases and/or interference of cytoskeleton organization which is known to play important roles in cell locomotion and capillary tube formation [88].…”
Section: Salvia Officinalis Salvia Officinalis L (Common Sagementioning
confidence: 99%
“…They have been found in breast cancer metastatic lymph nodes (Kim, Kang et al), and in colorectal metastases to the liver (Catarinella, Monestiroli et al). They can be identified by the expression of the TIE2 receptor on their surface which, curiously, is also expressed by blood vessel endothelial cells, where they are integral to angiogenic pathways and development (Plank andSleeman 2003, Matsubara, Kanto et al 2013). Recent research indicates that TEMs are recruited to the tumor microenvironment at an early phase of development.…”
Section: B Background On Macrophage Subtypesmentioning
confidence: 99%
“…The M1 extreme of the macrophage activation spectrum is commonly associated with inflammatory responses and tumoricidal activity by release of proinflammatory cytokines and oxygen species such as nitric oxide (NO), which encourage tumor cell apoptosis (Plank and Sleeman 2003) (Edin, Wikberg et al 2012). Its presence in the tumor microenvironment is correlated with reduced angiogenesis required to supply the increased tumor metabolic needs, and thus reduced tumor growth and survival (Yuan, Hsiao et al 2015) (Italiani and Boraschi 2014).…”
Section: B Background On Macrophage Subtypesmentioning
confidence: 99%
See 1 more Smart Citation